Myofibroblastoma of the breast - Sanmugasiva, Vithya Visalatchi; Ramli, Marlina Tanty; Fadzli, Farhana; Kaur, Shaleen; Abdul Rahman, Nazarina; Rahmat, Kartini (College of Pathologists, Academy of Medicine Malaysia, 2018)
Introduction: Myofibroblastoma is a rare benign mesenchymal tumour arising from the stromal elements of the breast tissue. Histopathological variants such as classic, cellular, collagenous / fibrous, lipomatous, infiltrative, myxoid and epithelioid have been identified. Most myofibroblastomas are immunoreactive for CD34, actin, CD10 and desmin, usually express oestrogen receptor (ER), progesterone receptor (PR) and variably express androgen receptor (AR). Case report: We report a case of myofibroblastoma in an octogenarian male presenting with painless solitary breast lump. Mammography (digital tomosynthesis) and ultrasound showed a well-circumscribed hyperdense mass and hypoechoic, solid, oval mass with peripheral vascularity respectively. Patient underwent wide local excision. Discussion: Diverse characteristics of myofibroblastoma on imaging necessitates histopathological analysis for an accurate diagnosis. Myofibroblastoma are often confused with fibroadenomas due to the benign imaging characteristics and with malignant neoplasia due to their wide morphological spectrum. Surgical excision is considered curative.